The impact of collaboration network on new product development: Evidence from the automobile industry of China - Peizhen Chen (Journal of Industry-University Collaboration (JIUC), 2019)
Purpose Researchers agree that collaboration networks can be an important implement in a firm's innovation process, but there is limited empirical evidence on actually how they facilitate the new product development (NPD). The paper aims to discuss these issues. Design/methodology/approach Using longitudinal and multisource data on a sample of firms engaged in the Chinese automobile industry, the authors examine the structural properties of collaboration networks and their possible influences on firms' NPD performance. Findings The results indicate that the structural features of the technology-based collaboration networks in the automobile industry have a low degree of collaborative integration and they influence firms' NPD performance in diverse ways. The authors find that the direct ties, indirect ties and structural holes of the collaboration networks are all positively associated with firms' number of new products. However, the authors have not found the evidence that the number of direct ties can moderate the relationship between the indirect ties and the NPD performance. Originality/value First, previous researches concerning the network mainly focused on their influence on technology innovation, few scholars studied the relationship between collaboration network and NPD. Second, the data used in this paper are true and valid, they are all from relevant departments of the Chinese government. Third, the empirical research of new products in China's manufacturing industry is relatively new.
Keywords: 330; China automobile industry; Collaboration network; New product development performance